Solar global horizontal and direct normal irradiation maps in Spain derived from geostationary satellites. (August 2015) - Polo, J.
Abstract: Solar radiation derived from satellite imagery is a powerful and highly accurate technique for solar resource assessment due to its maturity and to the long term database of observation images available. This work presents the methodology developed at CIEMAT for mapping solar radiation from geostationary satellite information and it also shows solar irradiation maps of global horizontal and direct normal components elaborated for Spain. The maps presented here have been developed from daily solar irradiation estimated for eleven years of satellite images (2001–2011). An attempt to evaluate the uncertainty of the presented maps is made using ground measurements from 27 meteorological stations available in Spain for global horizontal irradiation obtained from the World Radiation Data Centre. In the case of direct normal irradiation the ground measurement database was scarce, having available only six ground stations with measurements for a period of 4 years. Yearly values of global horizontal irradiation are around 1800 kWh m −2 in most of the country and around 1950–2000 kWh m −2 for annual direct normal irradiation. Root mean square errors in monthly means were of 11% and of 29% for global horizontal and direct normal irradiation, respectively. Highlights: Solar irradiation mapping in Spain is done from satellite information. 27 Stations were used to evaluate the uncertainty (11% in GHI). Satellite models are today a very useful tool for solar resource mapping.